WOOD DENSITY OF CLONES OF Eucalyptus urophylla x Eucalyptus grandis IN DIFFERENT CONDITIONS OF GROWTH - Mauri, Renata; Oliveira, José Tarcísio da Silva; Filho, Mário Tomazello; Rosado, Antônio Marcos; Paes, Juarez Benigno; Calegario, Natalino (Floresta, 2014)
Abstract Variations in the growth site of trees have influence on the internal structure of the trunk. Considering this fact, this study investigated influence of the characteristics of the growth site on wood specific gravity of two clones of Eucalyptus urophyllax Eucalyptus grandis, approximately six years old, growing in different altitudes and topographies. Furthemore, two methods of sampling of the wood specific gravity were studied, for comparison purpose. Results showed that wood specific gravity underwent variations between growth conditions andtrends in wood specific gravity variations, compared between growth conditions, were the same regardless of the clone. With relation to sampling method, the wedge was more appropriate for determination of wood specific gravity, in order to extrapolate the disc density. These results provide tools to forestry companies about consolidation of genetic material and its behavior in different growth conditions, to attend wood quality requirements. Keywords: Eucalypt; wood quality;topography; altitude. Resumo Densidade do lenho de clones de Eucalyptus urophylla x Eucalyptus grandis em diferentes condições de crescimento. As variações nas características do local de crescimento das árvores apresentam influência na estrutura interna do tronco. Diante deste fato, foi estudada a influência das características do local de crescimento na densidade básica da madeira de dois clones de EucalyptusurophyllaxEucalyptusgrandis, com aproximadamente seis anos de idade que cresceram emaltitudes e topografias diferentes. Além disso, estudou-se duas formas de amostragem da densidade básica na árvore para fins de comparações. Por meio dos resultados pode-seobservar que a densidade básica da madeira sofreu variações nas diferentes condições de crescimento e que as tendências de variações na densidade básica da madeira, frente às condições de crescimento, foram as mesmas independentemente do clone. Em relaçãoao método de amostragem,a cunha mostrou-se mais apropriada para determinação da densidade básica da madeira para fins de extrapolação da densidade do disco.Estes resultados fornecem subsídios para as empresas do setor florestal no que diz respeito à consolidação de material genético e seu comportamento em diferentes condições de crescimento para atender suas demandas de qualidade de madeira. Palavras-chave:Eucalipto; qualidade de madeira;topografia; altitude.